E-Commerce in times of pandemic: re-examining the role of key antecedents of Purchase Intention - Barra, Cristobal; Esquivel, Wilson; Medel, Allison; Melendez, Bastian (Estudios de Administración, 2022)
The objective of this research is to test a model for the formation of purchase intention in electronic commerce in the pandemic period, and in this way, to establish the similarities and differences that could be developed in the relationship of these variables with a context of normality. To carry out this objective, a model is proposed where trust and ease of use are the most relevant antecedents of online purchase intention. Then, on the one hand, the willingness to trust, privacy and security are considered as determinant variables of trust, while, on the other hand, utilitarian and hedonic characteristics are considered as determinants of ease of use. To test the model, a sample of 242 users of electronic commerce platforms in Chile was obtained and the relationships were analyzed using a structural equation model. As a result, it was possible to verify that the effect of trust and ease of use are verified in this context, but a greater effect of the second variable with respect to the first is striking. In addition, it was found that the effect of the willingness to trust and privacy on trust is not significant, as is the effect of hedonic characteristics on ease of use, giving a leading role to security and utilitarian characteristics in the model. The results help administrators to point their management objectives towards these variables in order to improve the purchase intention of consumers.